Learning science in an integrated classroom: Finding balance through theoretical triangulation - Rennie, Leonie; Venville, G.; Wallace, J. (Taylor and Francis Group, 2010)
The central thesis of this paper is that the learning of science in integrated curricular contexts requires a broader theoretical framework than is typically adopted by researchers and teachers. The common practice of interpreting science learning in terms of conceptual and procedural understandings in such contexts is problematized through an examination of the literature. As an alternative to the traditional approach, a triangulation of three theoretical perspectives is undertaken to view the science learning in a classroom case study of integrated curriculum. The conclusion highlights the necessity of balance between the disciplinary forces on curriculum and the forces that better reflect the multiple dimensions of learning in the real world. The use of theoretical triangulation is demonstrated as a technique through which a balanced, and more complete, view of learning in integrated contexts can be achieved.